Linking business analytics capability and sustainability performance: The mediating role of circular economy implementation - Francis Kamewor Tetteh; Gabriel Atiki; Andrews Kyeremeh; Francisca Delali Degbe; Prosper Apanye (Modern Supply Chain Research and Applications, 2024)
Purpose Though business analytics capability continues to attract considerable industrial and scholarly attention, its holistic performance implications, especially in the post-COVID-19 period, have not been fully understood. Thus, there have been calls for a full understanding of the implications of BAC for achieving holistic, sustainable outcomes among firms. This study therefore examines the influence of BAC on the three dimensions of sustainable performance. We also proposed the mediating role of circular economy implementation. Design/methodology/approach We tested the proposed model using survey data from 246 managers of manufacturing firms in Ghana. Partial least squares structural equation modelling was employed to validate the model. Findings Our findings showed that BAC significantly enhances both sustainable performance and circular economy implementation. We also found a significant association between CEI and sustainable performance. We further found significant partial mediation of CEI in the BAC sustainable performance nexus. Practical implications Our study offers thoughtful insights for managers, policymakers and the academic community that firms should simultaneously implement circular models alongside building analytics competencies in the quest to achieve balanced performance outcomes. Originality/value To the best of our knowledge, our study is among the very few attempts to understand the mechanism that channels the benefits of BAC for a holistic, sustainable outcome.
Keywords: 650; Business analytics capability; Circular economy implementation; Sustainable performance